Portrait of Metabolic Syndrome by Gender in A Rural Area of Gowa Regency - Sadarang, Rimawati Aulia Insani; Bujawati, Emmi; Wijaya, Dian Rezki; Ansyar, Dian Ihwana; Haerana, Bs Titi; Nildawati, Nildawati (Diversity: Disease Preventive of Research Integrity, 2024)
Metabolic syndrome is an important indicator in efforts to control non-communicable diseases. The incidence of metabolic syndrome is directly proportional to the incidence of obesity while the prevalence of metabolic syndrome varies based on sociodemographic characteristics and lifestyle. Efforts to identify metabolic syndrome in the community are a crucial step to identify early the potential for hypertension, coronary heart disease, stroke and diabetes mellitus. This study aims to identify components of metabolic syndrome based on gender. Cross sectional study is the research design that underlies data collection on risk factors for metabolic syndrome which is carried out through interviews and measurements of height, weight, waist circumference, blood pressure and cholesterol levels using NCEP-III criteria as the basis for identifying metabolic syndrome. Data analysis used the Chi-Square test. The metabolic syndrome component in the form of obesity is identified in men and women using different indicators. Both men and women have experienced increases in systolic blood pressure and cholesterol levels. A history of smoking was the only risk factor for metabolic syndrome with a statistically significant difference in proportion between men and women. Behavioral modifications such as eating patterns, rest, and others according to the guidance of the Koran and hadith are needed to minimize the incidence of metabolic syndrome.